2003
DOI: 10.2466/pms.2003.97.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Age and Understanding Speakers with Spanish or Taiwanese Accents

Abstract: This pilot study concerned the intelligibility of accented speech for listeners of different ages. 72 native speakers of English, representing three age groups (20-39, 40-59, 60 and older) listened to words and sentences produced by native speakers of English, Taiwanese, and Spanish. Listeners transcribed words and sentences. Listeners also rated speakers' comprehensibility, i.e., listeners' perceptions of difficulty in understanding utterances, and accentedness, i.e., how strong a speaker's foreign accent is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Thus, one could expect older adults to experience even greater difficulties than younger adults when presented with accented speech. However, most work focusing on this question confirms that while adults do have greater difficulty with accented than unaccented speech, the size of this effect is not significantly greater for older than younger listeners (Burda et al, 2003; Shah et al, 2005; Ferguson et al, 2010; Gordon-Salant et al, 2010a). It does not appear that the absence of a difference across age groups could be due to a ceiling effect (Adank et al, 2009; put forward a similar argument to explain data collected from younger listeners).…”
Section: Accent Perception In Late Adulthoodmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, one could expect older adults to experience even greater difficulties than younger adults when presented with accented speech. However, most work focusing on this question confirms that while adults do have greater difficulty with accented than unaccented speech, the size of this effect is not significantly greater for older than younger listeners (Burda et al, 2003; Shah et al, 2005; Ferguson et al, 2010; Gordon-Salant et al, 2010a). It does not appear that the absence of a difference across age groups could be due to a ceiling effect (Adank et al, 2009; put forward a similar argument to explain data collected from younger listeners).…”
Section: Accent Perception In Late Adulthoodmentioning
confidence: 98%
“…First, perhaps different studies sample from a diverse population without considering variables that would structure this variability. Subsequent work has more explicitly attempted to control for differences in hearing status (e.g., Burda et al, 2003; Ferguson et al, 2010), which is usually found not to interact with accented speech perception (but see Gordon-Salant et al, 2010b for a more complex pattern of results; and Janse and Adank, 2012, for contrary results). However, there is still some progress to be made in understanding the effects of cognitive decline, and its contribution to the diversity of results reported.…”
Section: Accent Perception In Late Adulthoodmentioning
confidence: 99%
“…Naturally, these mismatches can lead to a reduction in the intelligibility of the speech (Gass and Varonis, 1984; Munro and Derwing, 1995; Bent and Bradlow, 2003; Burda et al, 2003; Ferguson et al, 2010; Gordon-Salant et al, 2010a,b). However, even when foreign-accented speech is fully intelligible to listeners (i.e., they can correctly repeat or transcribe it), processing it requires more effort than processing native accents: listeners report that accented speech is more difficult to understand (Munro and Derwing, 1995; Schmid and Yeni-Komshian, 1999), and it is processed more slowly (Munro and Derwing, 1995; Floccia et al, 2009) and comprehended less well than native-accented speech (Anderson-Hsieh and Koehler, 1988; Major et al, 2002).…”
Section: Listening Effort and Accented Speechmentioning
confidence: 99%
“…These duration changes, in conjunction with age-related losses in temporal sensitivity, could lead to processing difficulties for older listeners when presented with unfamiliar stress patterns within samples of speech (e.g., accented speech). Research on this topic is presently limited in scope, although at least one investigation reports that older listeners do have problems recognizing accented English sentences (Burda et al, 2003). This observation points to a need for more information about the attributes of accented sound sequences that influence processing performance among older listeners.…”
Section: Introductionmentioning
confidence: 99%